2021
DOI: 10.3389/fgene.2021.673951
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Mitochondrial Genome Editing for Human Fertility Health

Abstract: Mitochondrial DNA (mtDNA) encodes vital proteins and RNAs for the normal functioning of the mitochondria. Mutations in mtDNA leading to mitochondrial dysfunction are relevant to a large spectrum of diseases, including fertility disorders. Since mtDNA undergoes rather complex processes during gametogenesis and fertilization, clarification of the changes and functions of mtDNA and its essential impact on gamete quality and fertility during this process is of great significance. Thanks to the emergence and rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 171 publications
(229 reference statements)
0
7
0
1
Order By: Relevance
“…In the gene-editing era, mitochondrial genome editing (MGE) seems to be one of the possible solutions. MGE refers to the modification of human oocytes or embryos with intracytoplasmic microinjection or mitochondria-targeted nucleases in order to prevent transmission of mitochondrial diseases [ 93 ]. Yahata et al [ 94 ] engineered platinum TALENs, which were transported into mitochondria, recognized the mtDNA sequence including the m.13513 position, and preferentially cleaved G13513A mutant mtDNA, and conducted an experiment with induced pluripotent stem cells (iPCs).…”
Section: Clinical Usefulness Of Assessing and Improving Mitochondrial...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the gene-editing era, mitochondrial genome editing (MGE) seems to be one of the possible solutions. MGE refers to the modification of human oocytes or embryos with intracytoplasmic microinjection or mitochondria-targeted nucleases in order to prevent transmission of mitochondrial diseases [ 93 ]. Yahata et al [ 94 ] engineered platinum TALENs, which were transported into mitochondria, recognized the mtDNA sequence including the m.13513 position, and preferentially cleaved G13513A mutant mtDNA, and conducted an experiment with induced pluripotent stem cells (iPCs).…”
Section: Clinical Usefulness Of Assessing and Improving Mitochondrial...mentioning
confidence: 99%
“…Moreover, Yang et al [ 95 ] demonstrated successful elimination of m.3243A>G mutation in iPCs via injection of mitoTALEN mRNA. However, protein engineering and assembly processes for every genomic target seem to be a time-consuming task [ 93 ]. On the other hand, CRISPR/Cas9 genome editing technology was also suggested to target mutant mtDNA [ 96 ].…”
Section: Clinical Usefulness Of Assessing and Improving Mitochondrial...mentioning
confidence: 99%
“…Though still not available for clinical use, new therapies using mitochondrial genome editing [32], which would avoid both the third-party (oocyte donor) participation and the discomfort related to the patient's oogonia stem cell recovery, are currently under investigation. It is important to accommodate existing genome editing techniques that are successfully used for nuclear DNA and to make them effective in the case of mtDNA.…”
Section: Mitochondrial Genome Editingmentioning
confidence: 99%
“…With the development of nuclear gene editing technology, the question now arises regarding how to target their actions to mtDNA instead of nuclear DNA. First demonstrated in 2012 [32], CRISPR/Cas9 genome editing technology became a revolutionary tool for nuclear gene editing. Further research suggests that Cas9 can be easily programmed by a guide RNA (gRNA) to act in different cellular targets.…”
Section: Mitochondrial Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation